2021
DOI: 10.3389/fbioe.2021.761846
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Pre-vascularized 3D Lung Cancer Model in Fibrin Gel—Influence of Hypoxia and Cancer-Specific Therapeutics

Abstract: Lung cancer is the most frequently diagnosed cancer worldwide and the one that causes the highest mortality. In order to understand the disease and to develop new treatments, in vitro human lung cancer model systems which imitate the physiological conditions is of high significance. In this study, a human 3D lung cancer model was established that features the organization of a tumor with focus on tumor angiogenesis. Vascular networks were formed by co-culture of human umbilical vein endothelial cells and adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Their presence in the tumor culture not only supports the formation of intact cellular assemblies but also offers an opportunity to directly assess angiogenic properties in vitro 49 , 50 and the activity of antiangiogenic inhibitors. 51 We studied the typical morphology of Ad-MVs and their ability to enhance some vascular network formation within our PDT model ( Figure 4 A). On day 7 of the PDTs formation, the vascular network within the PDTs was characterized with UEA-1 lectin and CD31 staining.…”
Section: Resultsmentioning
confidence: 99%
“…Their presence in the tumor culture not only supports the formation of intact cellular assemblies but also offers an opportunity to directly assess angiogenic properties in vitro 49 , 50 and the activity of antiangiogenic inhibitors. 51 We studied the typical morphology of Ad-MVs and their ability to enhance some vascular network formation within our PDT model ( Figure 4 A). On day 7 of the PDTs formation, the vascular network within the PDTs was characterized with UEA-1 lectin and CD31 staining.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it was widely applied in research fields including new drug screening, tumour cell system biology, stem cell research and functional tissue implantation [46][47][48]. Additionally, previous findings indicated that the phenotype of the 3D lung cancer tumour sphere in vitro is closer to that of real cancer tissue in vivo [49,50]. Thus, it is considered a reasonable method to evaluate the in vivo efficacy of active compounds in the early stages of new drug development [51].…”
Section: In 3d Spheroid Cell Inhibition Assaymentioning
confidence: 99%
“…In vitro, a hydrogel material can be created by mixing fibrinogen with thrombin and calcium ions [99][100][101]. Fibrin-based hydrogels, renowned for their ability to promote vasculogenesis, are commonly employed in various models of vascularization due to their ease of fabrication [99,100,[102][103][104][105]. Furthermore, fibrin can be recovered from blood for the creation of autologous hydrogel, which ensures that viable implants can be used therapeutic applications [106].…”
Section: Naturally Derived Hydrogelsmentioning
confidence: 99%